Cognitive And Linguocultural Features of The English Wedding Ceremony (Zien Journal of Social Sciences and Humanities, 2021)
This article analyzes the most pressing issues in linguoculturology and cognitive linguistics as well as the features of the connotation of national consciousness in the field of culture and communication. During the analysis, the concepts that are understood in modern linguistics as components of human consciousness are clarified to the interests that maintain the sum of human knowledge about certain phenomena of the world and are part of national culture. Representatives of cognitive linguistics and linguoculturology touched upon the contextual system, collisions and individual cultural experiences reflected in the consciousness of a person in the form of a dictionary view of the world.